RESPONSE OF SOME HERBACEOUS PLANTS TO DIFFERENT GROWING MEDIA AND POTASSIUM SILICATE FOLIAR SPRAYING IN (LWS) - A. M. S. Zalzala,; S. A. Abdul Latif, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to conduct one of the vertical garden systems , selecting suitable plant species that with stand the climate conditions of Baghdad city in outer space to determine the appropriate growing medium for the (LWS), and to assess the impact of spraying with potassium silicate on the resistance of the cultivated plants to heat stresses . The study carried out at at Al-Batool Park of (Al-Kadhimiya Holy City). Two experiments were carried out, each one with a different plant species, including Wedelia trilobata and Tradescantia pallida, during the winter season of 2021 and summer season of 2022. The experiments were designed using a split block design. The experiments included two factors, the first being the growing medium, peatmoss + Perlite (50:50%) (M1), Vermicompost + Perlite (50:50%) (M2), Water hyacinth Compost + Perlite (50:50%) (M3), and Wheat Straw Compost + Perlite (50:50%) (M4). The second factor included spraying shoots with three levels of potassium silicate, (S), which were 0 ml/L (S0), 1.5 ml/L (S1), and 3 ml/L (S2). The results showed that using media M2, M3, and S2, as well as the interaction between them, was superior effect on the vegetative characteristics of the two plants. These treatments were successful in cultivating plants in (LWS) and covering the panels planted in it.